Max Weber vs Émile Durkheim: Pertarungan Paradigma dalam Sosiologi Hukum di Indonesia - Isdiyanto, Ilham Yuli (Jurnal Hukum & Pembangunan, 2025)
This study compares the thoughts of Max Weber and Emile Durkheim in the field of sociology of law and their relevance to the development of law in Indonesia. Weber emphasizes formal rational law through a positivistic approach, highlighting individual rationality in shaping social structures. In contrast, Durkheim views law as a tool of social solidarity rooted in morality and collective norms. This study employs a normative method integrated with hermeneutic philosophy, delving into the meaning of legal concepts through an in-depth interpretation of doctrines, theories, and legal literature. A descriptive-narrative analysis is conducted to understand the historical, social, and philosophical contexts of these two perspectives, enriched with visualizations for deeper comprehension. The findings indicate that Weber's approach is relevant for supporting legal and economic development, whereas Durkheim's perspective is more applicable for accommodating the plurality of customary law or living law. This article recommends integrating both approaches to establish a legal system in Indonesia that is responsive to social diversity and adaptive to the demands of national development.